Plasma markers of oxidative status were associated with increasing continuous cardiometabolic risk scores in healthy students aged 16–20 years without central obesity - Koborová, I; Gurecká, R; Csongová, M; Šebek, J; Šebeková, K (Acta Paediatrica, 2018)
Aim We studied the association between increased cardiometabolic risk and markers of oxidative status and glycation in apparently healthy subjects who did not present with central obesity. Methods From 2011 to 2012, we recruited 2064 students (53% girls) aged 16–20 years from Western Slovakia. Their continuous metabolic syndrome scores (MSS) were calculated as a mean of the sum of the z‐scores of waist‐to‐height ratio, mean arterial pressure, triacylglycerols, high‐density lipoprotein‐cholesterol and quantitative insulin sensitivity check index. Plasma markers of protein glycation and oxidation, lipid peroxidation and total antioxidant status were analysed. Results In both genders, advanced oxidation protein products (AOPPs) increased across the MSS quintiles (p < 0.001). AOPPs and fructosamines were significant predictors of the MSS in both genders. Moreover, high‐sensitivity C‐reactive protein, leukocyte counts and advanced glycation end‐products (AGEs) contributed significantly in girls. Triacylglycerols, fructosamines, AGEs and total antioxidant capacity correlated significantly with AOPPs in both genders. Conclusion Advanced oxidation protein products may act as inflammatory mediators that contribute to the development of cardiometabolic afflictions. Determining these may provide information related to cardiometabolic risk and represent potential target to reduce or prevent irreversible oxidative stress‐induced cellular damage.